Russian-Ukrainian War. Insights from modern conflicts focusing on the Polish Territorial Defense Forces through a polemology and irenology approach - Magdalena El Ghamari (Journal of Modern Science, 2025)
Objectives This study explores the impact of the Russo-Ukrainian War on Poland’s Territorial Defence Forces (TDF), focusing on their adaptation to hybrid threats and expanded civil-military roles. Through comparison with defence models in Finland, Israel, and Ukraine, it proposes measures to strengthen resilience, decentralisation, and societal integration.